Redesigning for Disassembly and Carbon Footprint Reduction: Shifting from Reinforced Concrete to Hybrid Timber-Steel Multi-Story Building - Morales-Beltran, Mauricio; Engur, Pinar; Sisman, Omer Asim; Aykar, Gizem Nur (Mdpi, 2023)
To reduce carbon emissions, holistic approaches to design, plan, and build our environment are needed. Regarding multi-story residential buildings, it is well-known that (1) material choices and construction typologies play a fundamental role in the reduction of carbon footprint, (2) shifting from concrete to timber will reduce significantly the carbon footprint, and (3) a building designed to be disassembled will increase the potential of achieving zero-carbon emissions. However, little has been said about the consequences of such shifts and decisions in terms of building architecture and structural design, especially in seismic-prone regions. In this study, an existing 9-story reinforced concrete (RC) multi-story residential building is redesigned with cross-laminated timber floors and glue-laminated timber frames for embodied carbon reduction purposes. Firstly, the reasons behind design decisions are addressed in terms of both architecture and structure, including the incorporation of specially steel concentrically braced frames for seismic-resistance. Then, the outcomes of life cycle assessments and pushover analyses show that the RC residential building emits two times more carbon than the hybrid steel-timber residential building, and that while the hybrid building's lateral load-capacity is less than in the RC building, its deformation capacity is higher. These results highlight the relevance of considering the carbon footprint in combination with the design decisions, which seems to be the key to introducing circular projects in seismic-prone areas.
Keywords: embodied carbon; buildings; structural design; construction technology; architectural materials; life cycle assessment; seismic performance; Turkey